EVALUATION OF ENVIRONMENTALLY FRIENDLY LEVEL FISHING GEAROPERATING IN INDRAGIRI HILIR WATER PROVINCE RIAU (CASE STUDY OF TANAH MERAH VILLAGE TANAH MERAH DISTRICT) - Sri Devi; Bustari Bustari; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was conducted in January 2019 in Tanah Merah Village Tanah Merah District Indragiri Hilir Regency Riau Province. The purpose is to evaluate level of friendliness of the gill nets operating in Tanah Merah Village with 9 FAO criteria in CCRF (1995) modified by Monintja (2001) supported by 5 aspects of sustainable fishing (CCRF). Based on the results evaluation of fishing gear, there are two types of gill nets operated by fishermen, namely lomek nets and belanak nets. The results showed that the lomek net was very environmentally friendly by obtaining a score of 30.95 and sustainable. Whereas belanak nets only occupy an environmentally friendly position by obtaining a score of 27.2 and sustained. Keywords: Gill net, Food and Agriculture Organization, Code of Conduct for Responsible Fisheries